2013
DOI: 10.1111/hepr.12094
|View full text |Cite
|
Sign up to set email alerts
|

Utility of controlled attenuation parameter measurement for assessing liver steatosis in Japanese patients with chronic liver diseases

Abstract: The CAP is a promising tool for rapidly and non-invasively diagnosing steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 50 publications
3
40
0
3
Order By: Relevance
“…However, such excellent results have not been reproduced in most subsequent studies. Overall, the performance of CAP was good for the diagnosis of hepatic steatosis grade ≥ S1 with AUROC of 0.79–0.89, but it was only fair for steatosis grade ≥ S2 and S3 with AUROC of 0.72–0.79 and 0.70–0.76, respectively …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, such excellent results have not been reproduced in most subsequent studies. Overall, the performance of CAP was good for the diagnosis of hepatic steatosis grade ≥ S1 with AUROC of 0.79–0.89, but it was only fair for steatosis grade ≥ S2 and S3 with AUROC of 0.72–0.79 and 0.70–0.76, respectively …”
Section: Discussionmentioning
confidence: 96%
“…This is called controlled attenuation parameter (CAP), and it has been suggested to correlate well with hepatic steatosis . Several publications have explored CAP for estimation of hepatic steatosis in patients with chronic liver disease . All of these studies were on patients with chronic liver disease of various etiologies with limited number of NAFLD patients, except one study that consisted of a homogeneous cohort of chronic hepatitis C patients .…”
Section: Introductionmentioning
confidence: 99%
“…and its potential confounding factors have yet to be determined for an accurate J Gastrointestin Liver Dis, March 2015 Vol. 24 No 1: [35][36][37][38][39][40][41][42] interpretation of its results. In addition, studies taking into consideration the skin-capsule distance would be of great importance, since a distance above 25 mm may lead to overestimation of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…24 No 1: [35][36][37][38][39][40][41][42] The current "gold standard" for evaluating steatosis is liver biopsy (LB), but it is invasive and may result in severe complications [8]. Furthermore, LB has potential sampling errors and cannot be readily repeated for adequate patient follow-up [9].…”
Section: Introductionmentioning
confidence: 99%
“…This method is simple, highly reproducible, and can be completed in an outpatient setting with no significant expertise . Some studies, with small patient populations, have suggested promising results for monitoring steatosis severity . In the present study, we conducted a meta‐analysis to assess the performance of CAP for the detection of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%